(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The micro, small and medium enterprises (MSMEs) sector in India is the major contributor of GDP in the country. These MSME’s are the foundation for the country’s GDP and catalyst in the growth engine and success of big corporates and multinationals in India. Two major people management issues faced by MSME’s are to find attract and retain suitable employees. It is imperative to have strong Human resource management practices in MSME’s to leverage, grow and sustain the disruption in the market place. There are multiple HR challenges for MSME’s in India and specifically in Pune. The objective is to measuring the linkages between HR dimensions of MSME’s and organizational performance and to study implementation of HR practices in MSME by IT, Manufacturing and service sector.